On different planes : an organizational analysis of cooperation and conflict among airline unions - Walsh, David J., 1956- (Cornell studies in industrial and labor relations, 1994)
How do unions learn to get along with each other? What factors compel them to work together and what factors tend to prevent cooperation? How do inter-union activities affect labor relations outcomes? Changed and threatening circumstances have forced those committed to the labor movement in the United States to address these questions. David Walsh sets a model for the process with his examination of unions in the airline industry, where the need for cooperation has been heightened in the era since deregulation. While the airline industry has a high rate of unionization, tradition and formal structures have hindered ties between unions.